Directive acts uttered by main character in I care a lot movie - Fanny Virginia; Ambalegin Ambalegin (Politeknik Negeri Bali, 2021)
This descriptive qualitative research essentially aimed at exploring the types of directive acts uttered by the main character in I Care a Lot movie. The data were taken from utterances of directive acts uttered by Marla as the main character. It was analyzed by applying the types of directive acts theory carried out by Searle (1979). The method of collecting the data was the observational method and non-participatory technique. Furthermore, pragmatic identity method and pragmatic competence- in equalizing were conducted to analyze the data. The results revealed that there were 15 utterances of directive acts uttered by the main character in I Care a Lot movie. There were 5 data showed asking, 4 data showed ordering, 3 data showed permitting, 1 data showed advising, 1 data showed requesting, and 1 data showed inviting. The type of asking became the commonly produced type because the main character frequently asked questions to other characters in I Care a Lot movie.